Handbook of polymer composites for engineers - Hollaway, L. (Woodhead Publishing Ltd, 1994)
This book introduces the engineer to fibres and polymer matrices, which are the components of the polymer composites for structural engineering. The authors also provide a simple guide, in tabular form, to the principal fabrication techniques, the basic design formulae, and the methods for structural composites systems and connections. This book introduces the engineer to fibres and polymer matrices, which are the components of the polymer composites for structural engineering. The authors also provide a simple guide, in tabular form, to the principal fabrication techniques, the basic design formulae, and the methods for structural composites systems and connections.
Electronic book text.
Keywords: Polymeric composites.; elektronické knihy; electronic books